Underuse and unawareness of residential respite care services in dementia caregiving: constraining the need for relief - Brandão, Daniela (2020)
This article describes an analysis of the use of residential respite care services and the factors that influence the use of such services among informal caregivers of people with dementia. The authors studied a sample of 223 caregivers participating in a community-based intervention project in northern Portugal. Participants provided information on their overall caregiving situation and on their use or willingness to use respite care services. Results showed that fewer than 6 percent of caregivers accessed the services and that although most caregivers were not familiar with these services, they recognized their importance and strongly considered the possibility of using them. Part-time care, lower levels of gratification, higher burden, and the care receiver's attendance of day center supported the willingness to use residential respite services. The limited offer, not knowing about the services, and cultural issues related to the family duties within the caregiving role can explain the low use of these services. Social work professionals have an important role in promoting residential respite care services, and thereby helping to reduce caregiving overload.